The Genetic Landscape of Diamond-Blackfan Anemia. - Ulirsch, Jacob C; Verboon, Jeffrey M; Kazerounian, Shideh; Guo, Michael H; Yuan, Daniel; Ludwig, Leif S; Handsaker, Robert E; Abdulhay, Nour J; Fiorini, Claudia; Genovese, Giulio; Lim, Elaine T; Cheng, Aaron; et al. (Am J Hum Genet, 2019)

The Genetic Landscape of Diamond-Blackfan Anemia. - Ulirsch, Jacob C; Verboon, Jeffrey M; Kazerounian, Shideh; Guo, Michael H; Yuan, Daniel; Ludwig, Leif S; Handsaker, Robert E; Abdulhay, Nour J; Fiorini, Claudia; Genovese, Giulio; Lim, Elaine T; Cheng, Aaron; et al. (Am J Hum Genet, 2018)
Diamond-Blackfan anemia (DBA) is a rare bone marrow failure disorder that affects 7 out of 1,000,000 live births and has been associated with mutations in components of the ribosome. In order to characterize the genetic landscape of this heterogeneous disorder, we recruited a cohort of 472 individuals with a clinical diagnosis of DBA and performed whole-exome sequencing (WES). We identified relevant rare and predicted damaging mutations for 78% of individuals. The majority of mutations were singletons, absent from population databases, predicted to cause loss of function, and located in 1 of 19 previously reported ribosomal protein (RP)-encoding genes. Using exon coverage estimates, we identified and validated 31 deletions in RP genes. We also observed an enrichment for extended splice site mutations and validated their diverse effects using RNA sequencing in cell lines obtained from individuals with DBA. Leveraging the size of our cohort, we observed robust genotype-phenotype associations with congenital abnormalities and treatment outcomes. We further identified rare mutations in seven previously unreported RP genes that may cause DBA, as well as several distinct disorders that appear to phenocopy DBA, including nine individuals with biallelic CECR1 mutations that result in deficiency of ADA2. However, no new genes were identified at exome-wide significance, suggesting that there are no unidentified genes containing mutations readily identified by WES that explain >5% of DBA-affected case subjects. Overall, this report should inform not only clinical practice for DBA-affected individuals, but also the design and analysis of rare variant studies for heterogeneous Mendelian disorders.